Exploring Potential Factors Affecting ESP Students’ Oral Communication Skill in Speaking Class Across Gender - Mandasari, Mellati (Journal of English Education and Linguistics, 2025)
This study aims to explore the factors influencing English for Specific Purposes (ESP) students’ oral communication skills in speaking classes, with particular emphasis on gender differences among Public Administration students at STIA Lppn Padang. Employing a qualitative research approach, the study involved 32 Public Administration students enrolled in an ESP speaking course. Data were collected through classroom observations and semi-structured interviews. The findings reveal that female students demonstrated stronger oral communication performance than their male counterparts, as evidenced by higher levels of motivation, greater self-confidence, and more effective management of speaking anxiety. In addition, female students were more responsive to teacher support, more actively engaged in peer interaction, and better able to utilize the classroom environment to enhance their speaking skills. In contrast, male students showed lower engagement, limited preparation, and reduced confidence in oral communication tasks. These findings indicate that gender differences in ESP speaking performance are context-dependent and shaped by an interaction of psychological and social factors. Pedagogically, the results suggest the need for ESP instructors to adopt gender-responsive teaching strategies, such as varied speaking tasks, structured peer collaboration, and supportive feedback mechanisms, to promote equitable participation and enhance oral communication skills among all students.